Entrepreneurship of small and medium producers in the municipality of Fuentedeoro-Meta By Lizeth Villalba (GEON Journal (Management, Organizations and Business), 2015)
This paper presents a new path towards competitiveness and development of the agricultural sector in the Meta Department, through the Mayor of Bogotá that was aimed at strengthening productive business units through the implementation of the proposed corporatisation of the thousand two hundred small and medium producers in the municipalities of Acacias, Guamal, Cubarral, El Dorado, Fuentedeoro, Granada, Lejanías, San Juan de Arama and Villavicencio.
Keywords: Competitiveness; Development; Strengthening; Corporatization